Service Quality Dimension and Service Characteristics of Digitalized Carrier Transactions in National Capital Region: Basis for Enhanced Customer Service - Manaluz, Chester (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to examine the relationship between service quality dimensions and service characteristics influencing importer satisfaction with digitalized carrier transactions, as a basis for enhancing customer service within the logistics and maritime sector. Guided by service quality and customer satisfaction frameworks, a quantitative, descriptive–correlational research design was employed using structured survey questionnaires administered to purposively selected importers operating in the National Capital Region (NCR) of the Philippines. The service quality dimensions analyzed included responsiveness, speed, reliability, and value, while service characteristics covered customer service representatives, ocean transport, and digital systems. Descriptive and inferential statistical techniques were used to assess satisfaction levels, perceived difficulties, and relationships among variables. Results indicated that importers were generally satisfied with responsiveness, speed, and reliability, with value emerging as the strongest contributor to overall satisfaction. Service quality dimensions were found to significantly influence satisfaction with ocean transport and digitalization, while no significant relationship was observed with customer service representative performance. Despite favorable satisfaction levels, challenges related to communication gaps, system integration issues, customer service coordination, and delayed notifications were identified and were found to be systemic rather than dependent on importer size. The study concludes that while digitalized carrier transactions deliver substantial operational value, improvements in system interoperability, real-time communication, and alignment between digital platforms and customer service functions are necessary to enhance adoption and overall importer satisfaction.